Pathogenicity characteristics of different subgenotype pseudorabies virus in newborn piglets - Xu, Lei; Tao, Qian; Xu, Tong; Yang, Yanting; Zhang, Yang; Liu, Zheyan; Zhou, Yuancheng; Zhu, Ling; Xu, Zhiwen (Frontiers in Veterinary Science, 2024)
Pseudorabies virus is a major pathogen in the pig industry, causing substantial economic losses. The emergence of pseudorabies virus variant strains in China has led to extensive spread, raising concerns about their potential impact. However, the differences in pathogenicity between the classical strains and the variant strains of genotype II are not well understood. In this study, we isolated three pseudorabies virus strains to evaluate their replication characteristics and to examine the differences in virulence genes among various subgenotypes strains. Additionally, a piglet infection model was utilized to investigate the clinical features of infection, tissue tropism, and the inflammatory responses induced by these strains. Our results showed that the genotype II variant strains (MS, XJ, LS, and CZ) had significantly larger plaque sizes and higher replication capacities than the genotype II classical strain Fa. The animal experiments revealed significant differences in pathogenicity among the pseudorabies virus subgenotype strains, with the variant strains showing higher mortality rates, more severe clinical symptoms, increased nasal virus shedding, and a more robust inflammatory response compared to the genotype II classical strain. There were also notable differences in tissue tropism among the strains. In terms of tissue viral loads, the genotype II variant strains did not exhibit a significant advantage over the genotype I classical strain. Furthermore, our findings indicate that antibodies against the genotype II classical strains have a reduced neutralizing capacity against the genotype II variant strains. On the other hand, antibodies against the genotype II variant strains displayed similar neutralizing abilities against both classical and variant strains. Overall, these findings offer important insights into the distinctions among pseudorabies virus subgenotypes and their implications for the clinical control of pseudorabies virus infections in pig farming.